Sistem Informasi Manajemen Risiko pada PT. XYZ Framework ISO 31000: Risk Management Information System at PT. XYZ Framework ISO 31000 - Fairianto Alfandy Firmanza; Irfani Helga Kurniawan (Program Studi Teknologi Informasi, 2021)
Companies engaged in the transportation sector, especially public transportation in Indonesia, continue to seek ideas and innovations to pamper passengers and also seek to make passengers become subscribers which will provide benefits for the company. Research carried out by researchers is one form of evaluation of the services that have been provided by PT. XYZ to customers, where in this study the factors of customer satisfaction will be the focus point of the study. This study will be divided into 4 categories, namely vehicle factors, price factors, time speed factors and service factors. Where the four factors are factors that can affect customer satisfaction with PT.XYZ. The research method that will be used in this research is a combination of data sampling and descriptive analysis, so that this research can generate feedback from customers of PT.XYZ and also become the best service strategy to face the challenges of competitors who are increasingly competing